ENHANCING PARENTAL INVOLVEMENT IN COLLABORATIVE ACTIVITIES BETWEEN FAMILIES AND KINDERGARTENS THROUGH ACTION RESEARCH - Thi Anh Kieu, Le; Ho Uyen, Tran (HNUE Journal of Science: Journal of Educational Science, 2024)
The coordination between family and school has a great influence on the comprehensive development of a child’s personality, but in reality, the coordination between family and school still has many limitations such as lack of cooperation. There is a consensus on the concept of child education between teachers and parents, and coordination between family and school has not been carried out regularly and effectively. Through action research at Huong Duong Kindergarten, Lien Chieu District, Da Nang City, this study aims to solve some related issues as how to solve the problem of parents’ awareness of the importance of coordination between family and school, how to supplement and perfect forms of coordination between family and school, how to implement coordination between family and school conveniently and effectively. The effectiveness of the research includes improved awareness of teachers and parents about the importance of coordination between family and school, improved skills in planning coordinated activities between family and preschool teachers, the skills of teachers and parents in building and organizing children’s educational activities are gradually improving, and the level of parental participation in school coordination activities is more frequent.